2017
DOI: 10.1038/leu.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of systemic administration of Edmonston strain of measles virus genetically engineered to express the sodium iodide symporter in patients with recurrent or refractory multiple myeloma

Abstract: MV-NIS is an Edmonston-lineage oncolytic measles virus expressing the human sodium-iodide symporter--a means for monitoring by noninvasive imaging of radioiodine. Patients with relapsed, refractory myeloma who had explored all other treatment options were eligible for this Phase I trial. Cohort 1 was treated with intravenous MV-NIS, and Cohort 2 received cyclophosphamide two days prior to MV-NIS. Thirty-two patients were treated. Cohort 1 initially enrolled to 4 dose-levels without reaching MTD and subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 21 publications
1
120
0
1
Order By: Relevance
“…The complete disease remission seen in one of the patients enrolled in this study was reported earlier [14,17]. This patient had rapid tumor regression accompanied by documented tumor-selective replication of MV-NIS, evidenced by NIS imaging.…”
Section: Discussionmentioning
confidence: 58%
“…The complete disease remission seen in one of the patients enrolled in this study was reported earlier [14,17]. This patient had rapid tumor regression accompanied by documented tumor-selective replication of MV-NIS, evidenced by NIS imaging.…”
Section: Discussionmentioning
confidence: 58%
“…MV can infect 20 to 70% of memory cells, including B cells, T cells, and plasma cells in the lymphoid tissue and peripheral blood during the first 3 to 10 days after infection (7,10,24). Clinical trials of systemic administration of engineered MV for oncolytic therapy of multiple myeloma also demonstrated efficient entry of MV into the bone marrow and plasma cell infection (36). In wild-type MV infections, lymphocytes undergo rapid proliferation during immune activation (37), and lymphocyte counts (and other immunological markers) return to normal levels within weeks of infection.…”
Section: Experimental MV Infection Confirms a Decrease In Previously mentioning
confidence: 99%
“…After NIS expressed by OVs takes up the iodide isotope, OV localization can be monitored using single-photon emission computed tomography or positron emission tomography [26,167]. MV-NIS is an oncolytic MV expressing NIS, and it has entered clinical trials for the treatment of multiple myeloma [21].…”
Section: Monitoring Ov Replicationmentioning
confidence: 99%
“…Some OVs can cross the blood-brain barrier (BBB) to kill brain tumor cells, such as reovirus [7] and parvovirus H-1 (H-1PV) [8], and OVs can turn "cold" tumors into "hot" tumors, thereby increasing the cellular sensitivity to other immunotherapies [9,10]. To date, many OVs, including DNA viruses, such as adenovirus (AdV) [11,12], vaccinia virus (VACV) [13,14], herpesvirus [15,16], and parvovirus [17] and RNA viruses, such as reovirus [18,19], Newcastle disease virus (NDV) [20], and measles virus (MV) [21] (Table 1) have been evaluated for cancer treatment (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%